Edi Rama : work - Rama, Edi, 1964-; Carlier / Gebauer (Berlin, Germany); Kunsthalle Rostock; Nevada Museum of Art (Berlin: Hatje Cantz, 2019)
The oeuvre of the Albanian artist and prime minister Edi Rama (born 1964) is inseparable from his political career. During telephone conferences and meetings, he makes drawings and watercolors on copies of his schedule, his work notes, on minutes, faxes and items of correspondence. The art that he produces in the environs of national power forms an abstract journal, a vivid record of political life and the everyday tensions between power and art. Work presents Rama$1 (Bs drawings and ceramic sculptures, as well as a tapestry that was inspired by a similar tapestry in Rama$1 (Bs office in Tirana. Made up of more than 700 of Rama$1 (Bs drawings, the tapestry runs throughout the entire book, creating a connection between his works. Besides essays on Rama$1 (Bs work, the book also features a conversation with the artist. -- Amazon.com.s
Includes bibliographical references.
Texts in English and German.
Published to accompany an exhibition held at the Kunsthalle Rostock, November 18, 2018 - January 6, 2019: Carlier / Gebauer, January 26 - March 9, 2019; Nevada Museum of Art Reno, November 21, 2019 - April 1, 2020.
Keywords: Rama, Edi, -- 1964- -- Exhibitions; Rama, Edi, -- 1964-; Artists -- Albania -- Exhibitions; Arti shqiptar-Piktura-Ekspozita-Arti modern-Skulptura-Qeramika; Exhibition catalogs; Exhibition catalogs